Macroeconomic challenges and the resilience of emerging market economies in the 21st century - Joshua Aizenman (Asian Development Bank Institute (ADBI), 2020)
A growing share of emerging markets (EMs) uses hybrid versions of inflation targeting that differ from the IT regimes of the OECD countries. Real exchange rate and international reserve changes affect the policy interest rates in commodity countries, aiming to stabilize their real exchange rate in the presence of volatile terms of trade and heightened exposure to capital inflow/outflow shocks. Inflation targeting works well with independent central banks, yet fiscal dominance concerns may hinder the efficacy and independency of central banks. This suggests experimenting with the integration of monetary rules and fiscal rules, possibly linking these rules with the operations of buffers like international reserves and sovereign wealth funds (SWFs). The global financial crisis validated the benefits of countercyclical management of international reserves and SWFs in reducing the volatility of real exchange rates. Macroprudential policies may complement or even substitute buffer policies by reducing a country's balance sheet exposure to foreign currency debt, mitigating the risk of costly sudden stops and capital flight. A growing share of EMs is experiencing exposure to new financial technologies (fintech), providing cheaper and faster financial services and extending financial coverage to previously under-served populations. Deeper fintech diffusion may redirect financial intermediation from regulated banks to emerging fintech shadow banks, some of which may have a global reach. These developments, and the diffusion of cryptocurrencies promising anonymized payment systems, may hinder the effectiveness of monetary policy and eventually induce greater financial instability. States may encourage the diffusion of efficient financial intermediation in ways that benefit users while restricting the use of anonymized exchange and global monies to reduce the threat of a shrinking tax base and to maintain financial stability.
Keywords: F2; F3; F4; F6; 330; resilience; inflation targeting; fintech; financial stability and regulations